2007
DOI: 10.1642/0004-8038(2007)124[1439:sacpog]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Status and Conservation Priorities of Golden-Winged Warbler (Vermivora Chrysoptera) in North America

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 11 publications
0
40
0
Order By: Relevance
“…Creation of habitat for Golden-winged Warblers is critical for the conservation and management of the species in the Appalachian Mountains (Buehler et al 2007, Confer et al 2011). Indeed, we have shown that habitat availability at the mid-Appalachian scale is an important driving factor of Golden-winged Warbler abundance in regenerating stands in Pennsylvania and Maryland.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Creation of habitat for Golden-winged Warblers is critical for the conservation and management of the species in the Appalachian Mountains (Buehler et al 2007, Confer et al 2011). Indeed, we have shown that habitat availability at the mid-Appalachian scale is an important driving factor of Golden-winged Warbler abundance in regenerating stands in Pennsylvania and Maryland.…”
Section: Discussionmentioning
confidence: 99%
“…We predicted that warbler abundance would have a quadratic relationship to time since harvest Buehler 2001, Bulluck andBuehler 2008). Furthermore, we expected that warbler abundance would be positively related to herbaceous cover (Klaus and Buehler 2001, Confer et al 2003, Bulluck and Buehler 2008, Aldinger 2010, sapling density Lutz 2004, Martin et al 2007), and shrub cover (Confer et al 2003, Martin et al 2007, Aldinger and Wood 2014 but negatively related to distance to a microedge, i.e., patchy conditions (Rossell et al 2003, Buehler et al 2007). We predicted a positive or quadratic response between warbler numbers and residual basal area (Rossell 2001, Roth et al 2014).…”
Section: Analysesmentioning
confidence: 95%
See 3 more Smart Citations